Description of dynamics of the Tuzla Landslide and its implications for further landslides in the northern slope and shelf of the Cinarcik Basin (Marmara Sea, Turkey) - Gokceoglu, C.; Tunusluoglu, M. C.; Gorum, T.; Tur, H.; Gokasan, E.; Tekkeli, A. B.; Batuk, F.; Alp, H. (ELSEVIER, 2009)
Seismic and multi-beam bathymetric data from the northern shelf and slope of the Cinarcik Basin, which is generated by the North Anatolian Fault Zone (NAFZ) located in the easternmost basin in the Marmara Sea, were re-interpreted to better understand the future sub-marine landslide susceptibility. Seismic data indicate that upper surface of the sub-marine extension of the Paleozoic rocks has an NNE-SSW oriented basin and a ridge type morphology controlled by the secondary faults of the NAFZ. Basins are fulfilled by Plio-Quaternary sediments, which are cut by strike-slip faults on the shelf and slope. The thickness of basin deposits reaches up to 130 m toward the linear northern slope of the Cinarcik Basin. A relatively recent sub-marine landslide, the Tuzla Landslide, cuts the slope of the Cinarcik Basin. The detailed morphological investigation indicates that the Tuzla Landslide is a deep-seated rotational landslide, which was likely triggered by activity of the NAFZ. Morphological analyses also indicate that the thick Plio-Quaternary deposits on the Paleozoic basement slid during the Tuzla Landslide event. This landslide is considered as a key event to understand the dynamics of the potential landslides on the northern shelf and slope of the Cinarcik Basin. Two areas locating on the eastern and the western sides of the Tuzla Landslide are considered as the potential areas for future sliding due to similarities of geological and geomorphological features with the Tuzla Landslide such as similar thick Plio-Quaternary deposits, similar slope morphology, and similar fault activity cutting the sediments. Considering this information. the purposes of the present study are to determine the dynamics of the possible landslide areas and to discuss their effects on the sub-marine morphology. In the light of the interpretations, the amounts of possible displaced material are obtained. Three different landslide scenarios due to possible slide surfaces for future landslides are developed and assessed. The first scenario is sliding of the sediments at the shelf break. The third scenario is a mass movement of almost whole basin deposits on the Paleozoic rocks. The latter one is evaluated as less important because of the volume of the displaced material, and the latter one is accepted as lowest possible event. Among the scenarios, the second scenario is accepted as the most critical and possible because of the amount of the slipped material and existence of faults rupture, which is considered as further sliding surfaces. These landslides will result in important changes in shelf. slope and basin floor in the study area. Crown Copyright (c) 2009 Published by Elsevier B.V. All rights reserved.
Keywords: The Marmara Sea; Sub-marine landslide; Landslide dynamics; Susceptibility assessment; Earthquake; ANATOLIAN FAULT ZONE; BLACK-SEA; NW TURKEY; EVOLUTION; STRAIT; EARTHQUAKES; TECTONICS; ISTANBUL; BOSPORUS; SOUTH; Engineering; Geology